Analysis of the Use and Maintenance of Light Fire Extinguishers to Anticipate Emergency Situations on the MV. Tanto Berkat Ship - Muhammad Fajar Rezadrian; I'ie Suwondo; Dety Sutralinda; Ardhiana Puspitacandri (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Fire safety on board ships depends on the availability of portable fire extinguishers (APAR) as the initial means of extinguishing. This study aims to analyze the suitability of the use and maintenance of APAR and identify factors that influence its implementation on the MV. Tanto Berkat. The study used a qualitative approach with descriptive methods. The study population was all officers responsible for fire safety on board, while the sample was determined purposively, namely the Chief Officer, Second Officer, and Third Officer. The research instruments included semi-structured interview guidelines, observation sheets, and documentation. Data analysis used the interactive model of Miles, Huberman, and Saldaña through data reduction, data presentation, conclusion drawing, and triangulation of sources and techniques. The results of the study indicate that the use and maintenance of APAR have been carried out according to safety procedures through periodic inspections, fire drills, and maintenance records. However, some foam-type APARs were still found to be less easily accessible, periodic testing documentation was not optimal, and cleaning was inconsistent in several periods. In conclusion, the APAR use and maintenance system has met most of the SOLAS requirements, but improvements in documentation, accessibility, and maintenance supervision are still needed to improve preparedness for fire emergencies.